Fluorescence enhancement of gold nanoclusters via Zn doping for biomedical applications. Issue 14 (15th February 2018) - Qiao, Yanqing; Liu, Ying; Liu, Haixia; Li, Yonghui; Long, Wei; Wang, Junying; Mu, Xiaoyu; Chen, Jing; Liu, Haile; Bai, Xueting; Liu, Lingfang; Sun, Yuan-Ming; et al.
Abstract : Fluorescence enhancement of gold nanoclusters via Zn doping. Abstract : Gold nanoclusters (NCs) have been widely used in bioimaging and cancer therapy due to their unique electronic structures and tunable luminescence. However, their weak fluorescence prevents potential biomedical application, and thus it is necessary to develop an effective route to enhance the fluorescence of gold NCs. In this work, we report the fluorescence enhancement of ultrasmall GSH-protected Au NCs by Zn atom doping. The fluorescence signal of Zn-doped Au NCs shows approximately 5-fold enhancement compared to pure Au NCs. Density functional theory (DFT) calculation shows that Zn doping can enhance the electronic states of the highest occupied molecular orbital (HOMO), leading to enhancement of visible optical transitions. In vitro experiments show that AuZn alloy NCs can enhance the cancer radiotherapy via producing reactive oxygen species (ROS) and don't cause significant cytotoxicity. In vivo imaging indicates AuZn alloy NCs have significant passive targeting capability with high tumor uptake. Moreover, nearly 80% of GSH-protected AuZn alloy NCs can be rapidly eliminated via urine excretion.